2011
DOI: 10.1039/c1ob05679d
|View full text |Cite
|
Sign up to set email alerts
|

Proline-based reduced dipeptides as recyclable and highly enantioselective organocatalysts for asymmetric Michael addition

Abstract: A series of novel proline-based reduced dipeptides was developed and evaluated for a direct Michael addition of ketones and aldehydes to nitroalkenes. Excellent yields (up to 95%), diastereoselectivities (up to 98% dr) and enantioselectivities (up to 98% ee) were achieved in the presence of 5 mol% catalyst without any additional additives at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Interestingly, in the presence of a base in water the desired reactivity was observed yielding the final products 34 with moderate enantioselectivities. Notably, when the prolinamide moiety in the catalyst was replaced with a methylene group resulting in less rigid structure 41 h , much better results were obtained 24b. The squaramide moiety is another structural motif well recognized in hydrogen‐bonding catalysis in which the two NH groups are separated from each other by a two‐atom linker.…”
Section: Proline‐derived Double‐hydrogen‐bond‐ Donating Aminocatalystsmentioning
confidence: 99%
“…Interestingly, in the presence of a base in water the desired reactivity was observed yielding the final products 34 with moderate enantioselectivities. Notably, when the prolinamide moiety in the catalyst was replaced with a methylene group resulting in less rigid structure 41 h , much better results were obtained 24b. The squaramide moiety is another structural motif well recognized in hydrogen‐bonding catalysis in which the two NH groups are separated from each other by a two‐atom linker.…”
Section: Proline‐derived Double‐hydrogen‐bond‐ Donating Aminocatalystsmentioning
confidence: 99%
“…Chen [41] and his research group in 2011 had a different approach towards the effect of the carbonyl group of proline and proposed that the reduced forms of the proline dipeptides ( 48 ) (Figure 8b) offered better outcomes in conjugate addition reactions of cyclohexanones and nitrostyrenes. Comparison of the catalyst with/without chiral centre at δ ‐carbon revealed that the stereoselectivity depended entirely on the proline‘s second carbon.…”
Section: Proline‐dipeptide Derived Catalystsmentioning
confidence: 99%
“…While proline itself is not an efficient catalyst for Michael addition reactions, certain compounds derived from proline, such as (S)-2-trifluoromethylsulfonamidomethylpyrrolidine ( 1a ) developed by Wang et al, show excellent catalytic activity toward conjugate addition reactions. Particular attention has been given over the years to design short peptides, which have better catalytic activity than proline. Among them, peptides containing proline as one of the residues have gained notable success as organocatalysts.…”
Section: Introductionmentioning
confidence: 99%